2011
DOI: 10.1111/j.1439-0396.2011.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibre analysis and fibre digestibility in pet foods – a comparison of total dietary fibre, neutral and acid detergent fibre and crude fibre*

Abstract: Six dry dog foods and six dry cat foods with different carbohydrate sources were investigated in digestion trials. Food and faecal samples were analysed for CF, TDF and starch. In dogs, also neutral detergent fibre (aNDFom) and acid detergent fibre (ADFom) were analysed. N-free extract (NfE) was calculated for CF, and similarly for all other fibre analyses. Linear regressions were calculated between fibre intake and faecal fibre excretion. True digestibility was calculated from the regression coefficients [tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 43 publications
6
33
3
2
Order By: Relevance
“…solubility), but do not provide any information about their suitability for bacterial fermentation (de-Oliveira et al, 2011). Therefore, the combination of the chemical composition analysis with the in vitro gas production technique provides interesting complementary data about the ingredients.…”
Section: Discussionmentioning
confidence: 98%
“…solubility), but do not provide any information about their suitability for bacterial fermentation (de-Oliveira et al, 2011). Therefore, the combination of the chemical composition analysis with the in vitro gas production technique provides interesting complementary data about the ingredients.…”
Section: Discussionmentioning
confidence: 98%
“…This technical deficiency is proven in the evaluation of food for dogs and cats by the studying of Oliveira et al (2012) in which six dry dog foods and six dry cat foods were evaluated for fiber composition and digestibility, comparing a total dietary fiber, neutral and acid detergent fiber and crude fiber. The results demonstrated that crude fiber analysis did not correlate with any other method.…”
Section: Discussionmentioning
confidence: 99%
“…Based on laboratory results, the coefficient of total tract apparent digestibility of nutrients (CTTAD) of dry matter (DM), crude protein (CP), acid-hydrolyzed fat (AHF), organic matter (OM), nitrogen free extract (NFE), and gross energy (GE) were calculated according to the equation of Pond et al (1995).…”
Section: Digestibilitymentioning
confidence: 99%
“…Dry commercial foods for companion animals contain significant amounts of carbohydrates and these are mostly digestible, like starch. The part that is not digestible, denominated non-starch polysaccharides, is usually classified as dietary fiber (De-Oliveira, 2011). Physiologically, fibers are conceptualized as corresponding to food components that resist degradation by mammalian enzymes (Fischer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Diets with fibers are inserted into the animal feed according to their beneficial actions, such as control of various biochemical parameters in serum, i.e., glucose, triglycerides, and cholesterol (De-Oliveira, 2011). Studies show that dogs and cats that have their diet supplemented with different sources of fiber reduce postprandial blood glucose and cholesterol levels, and lose weight.…”
Section: Introductionmentioning
confidence: 99%